On the emerging flow from a dual-axial counter-rotating swirler; LES simulation and spectral transition. (25th January 2018) - Vashahi, Foad; Lee, Jeekeun
Highlights: Efficient local grid refinement method for LES-WALE simulation of a dual counter rotating swirler. Characterizing the mean flow field based on the flow swirl number. Statistical analysis on the relation of axial and tangential velocity components using correlation factor. Decay of number and magnitude of frequency peaks from inside of the swirler to the combustion chamber. Abstract: The LES of a dual counter-rotating axial swirler in a confined rectangular configuration was performed under cold flow conditions. As the first objective of this paper, the grids were constructed based on a primary RANS simulation and then refined relative the Kolmogorov length scale using a field function. This greatly aided the construction of a very fine and effective grid whereby all the required criteria for an LES could be met. For the sake of validation, results in terms of mean structures were compared to existing 2D PIV experimental data using water as the working fluid. The achievement of very good agreement between the results has presented the opportunity to study the flow behavior in unsteady state conditions. The available experimental facility suffers from a similar drawback and always results in measurements a few millimeters after the flare down to downstream, while the region before the flare with high swirling interaction remains inaccessible. The second objective of this study was to study the flow behavior merely within the region before the flare location. Previous investigations have shown that the inner axial swirler greatly reduces the interaction with the outer counter-rotating swirler; a few millimeters away from the swirler, there is no sign of the inner swirler motion. Additionally, previous studies have related the formation of Precessing Vortex Core (PVC) within the central core to the peaks of the pressure or axial velocity spectrum. In addition, in some cases, up to two distinct peaks have been reported at the swirler mouth [1–3] . However, the spectrum analysis under iso-thermal conditions at the region inside the swirler, where the inner swirler dominates the flow, showed a higher potential for instabilities, with three to four distinct peaks. It was observed that, moving forward, the number of peaks is decreased, and in certain areas where the experimental measurement is applicable, the number of peaks decreased to two and one distinct points. In addition, the co-variance of the identified regions of axial and tangential velocity showed a higher correlation. The data show that the central axis corresponds to a lack of peaks of instabilities, whereas further away in the radial direction, several peaks exist. These results both emphasize the importance of the region inside the swirler where the primitive mixture of fuel and swirling air is constructed and aid in identifying the source of instabilities.